Step
*
1
2
1
1
1
of Lemma
triangular-num-add1
1. n : ℕ
2. n rem 2 ≠ 1
3. ((n + 1) * ((n + 1) + 1)) = (((((n + 1) * ((n + 1) + 1)) ÷ 2) * 2) + 0) ∈ ℤ
4. (n * (n + 1)) = ((((n * (n + 1)) ÷ 2) * 2) + (n * (n + 1) rem 2)) ∈ ℤ
5. 0 ≤ (n rem 2)
6. n rem 2 < 2
⊢ ((n rem 2) * ((n rem 2) + 1) rem 2) = 0 ∈ ℤ
BY
{ ((Subst ⌜n rem 2 ~ 0⌝ 0⋅ THEN Reduce 0) THEN Auto) }
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  n  rem  2  \mneq{}  1
3.  ((n  +  1)  *  ((n  +  1)  +  1))  =  (((((n  +  1)  *  ((n  +  1)  +  1))  \mdiv{}  2)  *  2)  +  0)
4.  (n  *  (n  +  1))  =  ((((n  *  (n  +  1))  \mdiv{}  2)  *  2)  +  (n  *  (n  +  1)  rem  2))
5.  0  \mleq{}  (n  rem  2)
6.  n  rem  2  <  2
\mvdash{}  ((n  rem  2)  *  ((n  rem  2)  +  1)  rem  2)  =  0
By
Latex:
((Subst  \mkleeneopen{}n  rem  2  \msim{}  0\mkleeneclose{}  0\mcdot{}  THEN  Reduce  0)  THEN  Auto)
Home
Index